2017
DOI: 10.1016/j.homp.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Structural and thermal analyses of zinc and lactose in homeopathic triturated systems

Abstract: Our results suggested no structural changes due to the trituration and dynamization process. However, TG and DSC analyses permit the differentiation of dynamized and non-dynamized groups, suggesting the dynamization process induced a significant increase in the degradation heat. These results call for further calorimetric studies with other homeopathic dilutions and other methodologies, to better understand the dynamics of these systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Further calorimetric studies would enable greater understanding of the heat transfer from eddies to NPs during succussion. 48,49 The present study is limited, however, in the way the succussion was done manually, and therefore repeatability in achieving the same velocity field was not possible due to variation in mechanical forces used in each case. Different parameters of these processes, such as grinding energy, impact force, and number of impact strokes, need to be tuned to achieve greater uniformity in the results.…”
Section: Discussionmentioning
confidence: 97%
“…Further calorimetric studies would enable greater understanding of the heat transfer from eddies to NPs during succussion. 48,49 The present study is limited, however, in the way the succussion was done manually, and therefore repeatability in achieving the same velocity field was not possible due to variation in mechanical forces used in each case. Different parameters of these processes, such as grinding energy, impact force, and number of impact strokes, need to be tuned to achieve greater uniformity in the results.…”
Section: Discussionmentioning
confidence: 97%
“…Nanoparticle-Allostatic Cross-Adaptation-Sensitization (NPCAS) is a mechanism, proposed by Iris Bell and Mary Koithan, to explain the action of a homeopathic medicine. [4][5][6] This proposal was reinforced by the studies of Chikramane et al 7 in India and by Holandino et al 8 These authors observed nanoparticles (NPs) of the original substance in very highly diluted or lactose-succussed preparations of different homeopathic medicines. In Holandino's article, for instance, changes in enthalpy levels were detected after trituration of Zincum metallicum in lactose.…”
Section: Nanoparticle-allostatic Cross-adaptation-sensitization Modelmentioning
confidence: 93%
“…It is considered that there is a significant detection of molecules originating from the homeopathic matrix only in low dynamizations, but not in high or ultra-high dynamizations. The active principle of a dynamized medicines, which are also called of high dilutions or ultra high dilutions, possibly will be the information impregnated in the base substance that can be in one weak wave or several weak waves, not knowing if it would be, necessarily, exclusively an electromagnetic wave [32][33][34].…”
Section: Literature Review 21 the Biofield For Sciencementioning
confidence: 99%